DIETARY PATTERN AND LIFESTYLE OF ADULT COVID-19 SURVIVORS PRE AND POST COVID-19 INFECTION IN KARANGPILANG, SURABAYA - Andin Putri Kumalajati; Amalia Ruhana (JURNAL KESMAS DAN GIZI (JKG), 2022)
The COVID-19 pandemic has an impact on all aspects of life, especially health status which is influenced by dietary patterns and lifestyles on people. This study aims to determine differences in dietary patterns and lifestyles of adult COVID-19 survivors pre and post being infected with COVID-19. This type of research is quantitative with a cross-sectional study approach. The sample is COVID-19 survivors in Karangpilang District, Surabaya City, totaling 46 people by using purposive sampling technique. The collection of dietary data is a form of Food Frequency Questionnaire (FFQ) and lifestyle data is a form of lifestyle questionnaire. The analysis of differences in dietary patterns pre and post being infected with COVID-19 used the Wilcoxon test, while the analysis of differences in lifestyle pre and post being infected with COVID-19 used the McNemar test. The results showed that there were no significant differences in dietary patterns in the staple food groups (p=0,305), vegetable side dishes (p=0.483), animal side dishes (p=0.066), fruits (p=0.808), vegetables (p=0.662), commercial food (p=0.961), and beverages (p=0.671). In lifestyle, there were significant differences in the habit of washing hands with soap and running water (p=0.008), keeping a distance (p=0.004), sunbathing ± 15 minutes (p=0.001), and sleeping duration of 6-8 hours a day (p =0.000). In conclusion, there were no differences in the dietary patterns pre and post being infected with COVID-19 and in lifestyle there were significant differences in the habit of washing hands with soap and running water, keeping a distance, sunbathing for 15 minutes, and sleeping duration of 6-8 hours/day pre and post being infected with COVID-19.